PEMETAAN DATA MONOGRAFI KECAMATAN PRINGSEWU TAHUN 2014 - Koko Setiawan; Rosana Rosana; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2015)
This study attempted to make a thematic map by using data monographdistrict of Pringsewu in terms of (1) the location of the district office and village offices; (2) the location and number of public/private senior highschool; (3) the location of health infrastructure; (4) the population based on religion; (5) population density; (6) land use; (7) the number of industry and; (8) the number of acceptors KB. This research was using descriptive informative method. This research used the descriptive than informative method. The results of this research were; (1) a location map of district office and village offices; (2) a location map and the number of public/private senior high school; (3) a location map of health infrastructure; (4) a population map based on the religion; (5) a population of density map; (6) land use map; (7) a map of the number of industry and; (8) a map of the number acceptors KB.Penelitian ini bertujuan untuk membuat peta tematik dengan menggunakan data monografi kecamatan Pringsewu berupa data tentang (1) lokasi kantor kecamatan dan kantor desa/kelurahan; (2) lokasi dan jumlah SMA Negeri/Swasta; (3) lokasi prasarana kesehatan; (4) jumlah penduduk berdasarkanagama; (5) kepadatan penduduk; (6) penggunaan lahan; (7) jumlah industri serta; (8) jumlah akseptor KB. Penelitian ini menggunakan metode deskriptif informatif. Hasil dalam penelitian ini adalah (1) peta lokasi kantor kecamatan dan kantor desa/kelurahan; (2) peta lokasi dan jumlah SMA Negeri/Swasta; (3) peta lokasi prasarana kesehatan; (4) peta jumlah penduduk berdasarkan agama; (5) peta kepadatan penduduk; (6) peta penggunaan lahan; (7) peta jumlah industri serta; (8) peta jumlah akseptor KB.Kata kunci: pemetaan, monografi kecamatan, pringsewu.